Difração de feixes com simetria elíptica e possuindo momento angular orbital por uma abertura triangular isósceles - Melo , Leandro de Araújo (2017)
In this work it was investigated through the Fraunhofer diffraction pattern how to find the topological charge of beams possessing orbital angular momentum with elliptical symmetry. In order to perform such a procedure, the Mathieu beams, Ince-Gaussian beams and the Hermite-Gaussian vortex beams were used along whith various topological charge values l and different degrees of ellipsity, with the beam impinging on an isosceles triangular aperture. The numerical and experimental results agreed for a more complex symmetry case, in which the phase at the edges of the triangle instill has a quasi-linear growth, showing that the technique of the diffraction pattern by a triangular aperture make it possible to find the module and the signal of the topological charge in a simple way.